2017
DOI: 10.1093/mnras/stx2694
|View full text |Cite
|
Sign up to set email alerts
|

Mass models of NGC 6624 without an intermediate-mass black hole

Abstract: An intermediate-mass black hole (IMBH) was recently reported to reside in the centre of the Galactic globular cluster (GC) NGC 6624, based on timing observations of a millisecond pulsar (MSP) located near the cluster centre in projection. We present dynamical models with multiple mass components of NGC 6624 -without an IMBH -which successfully describe the surface brightness profile and proper motion kinematics from the Hubble Space Telescope (HST) and the stellar-mass function at different distances from the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
49
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 59 publications
10
49
2
Order By: Relevance
“…Our N-body simulations therefore confirm earlier results by Gieles et al (2018) who also found that no-IMBH is required to explain the observed surface brightness and velocity dispersion profile of NGC 6624. Models with IMBHs containing less than 5 per cent of the cluster mass in the form of an IMBH also provide acceptable fits to the velocity dispersion profile.…”
Section: Ngc 6624supporting
confidence: 90%
See 2 more Smart Citations
“…Our N-body simulations therefore confirm earlier results by Gieles et al (2018) who also found that no-IMBH is required to explain the observed surface brightness and velocity dispersion profile of NGC 6624. Models with IMBHs containing less than 5 per cent of the cluster mass in the form of an IMBH also provide acceptable fits to the velocity dispersion profile.…”
Section: Ngc 6624supporting
confidence: 90%
“…In addition, Perera et al (2017a, b) found evidence for a massive IMBH in NGC 6624 based on timing observations of several pulsars close to the cluster centre. However, Gieles et al (2018) were able to explain the observed period changes by a cluster model that did not contain an IMBH. In summary, there is currently no undisputed case for an IMBH in any Galactic globular cluster.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Other scenarios, invoking runaway collisions of massive stars and/or the collapse of a very massive star ( 200M ⊙ ) could also lead to the formation of IMBHs in globular clusters (e.g., Portegies Zwart & McMillan (2002), Gürkan et al (2004), Portegies Zwart et al (2004a), Portegies Zwart et al (2004b), Freitag et al (2006), Mapelli (2016), Gieles et al (2018b), and Section 3.2). A GW detection may be the most promising route to search for IMBHs in globular clusters, because a convincing detection with other methods remains elusive (Anderson & van der Marel 2010;Lanzoni et al 2013;Gieles et al 2018a;Tremou et al 2018; Amaro-Seoane 2018b).…”
Section: Globular Clustersmentioning
confidence: 99%
“…There has been an abundance of claims, usually followed by counter-claims, for the existence of IMBHs in large globular clusters. For example, see the studies of: G1, the most massive globular cluster around M31 (Gebhardt et al 2005;Miller-Jones et al 2012); ω Centauri, the most massive globular cluster around the Milky Way (Noyola et al 2008;Haggard et al 2013;Zocchi et al 2017Zocchi et al , 2019; plus other globular clusters around the Milky Way such as M15 (Gebhardt et al 2000;Gerssen et al 2002;Baumgardt et al 2003;Kirsten & Vlemmings 2012;den Brok et al 2014;Kirsten et al 2014); M54 (Ibata et al 2009); 47 Tucanae (Kızıltan et al 2017;Abbate et al 2018;Mann et al 2019);and NGC 6624 (Perera et al 2017;Gieles et al 2018;Baumgardt et al 2019). To date, there remains no conclusive evidence for IMBHs in globular clusters (Hurley 2007;Vesperini & Trenti 2010;Lanzoni & Cosmic-Lab Team 2016;Maccarone 2016;Wrobel et al 2016;Ferraro et al 2018;Tremou et al 2018), although see ).…”
Section: Introductionmentioning
confidence: 99%